The Use of Fast Counting Learning Media in an Effort to Increase Interest in Learning Mathematics for Low Grade Students - Muhammad Shaleh Assingkily; Annisa Saputri; Indah Purnama Siregar (Journal of Contemporary Islamic Primary Education, 2022)
This study aims to describe the use of fast counting learning media as an effort to increase interest in learning mathematics for lower grade students. The type of this research is qualitative using descriptive analytical study method. Obtaining data through observation, interview and documentation techniques. Furthermore, the data were analyzed using reduction techniques, data presentation, and drawing conclusions, as well as testing the validity of research data using triangulation techniques. The results of this study concluded that learning mathematics provides examples of cases to be solved by each student and must also be able to increase students' interest in learning mathematics. It can also create and create students' natural ability to solve problems. Thus, it forms creativity according to the potential of students. With the help of interesting learning media, it can foster students' enthusiasm and ability to solve problems.